Implementation of Pancasila Values in Environmental Law Enforcement - Gunawan, Adi; Suhaimi, Suhaimi; Umam, Khairul; Lina Rahman, Salsa Bila; Nadiv, Shafa (Institute for Law and Economics Studies, 2026)
Crimes against the environment are very common in Indonesia, some are included in the judicial process and some are untouched by the law. (1) As a legal state based on Pancasila, of course, for environmental crimes that enter the judicial institution, law enforcement is carried out based on Pancasila, especially the principle of justice; (2) This research is a literature research, with a qualitative discussion method, with secondary data that examines laws and regulations, judges' decisions and theories related to the object of the problem; (3) Based on the results of research that has been conducted, the development of theory and legal knowledge of the principle of justice is developing towards the environment, namely environmental justice, although in the legislation the concept of theory has been accommodated in the rules, but in law enforcement it still does not lead to environmental justice; (4) To date, environmental law enforcement in Indonesia has yet to achieve environmental justice, and law enforcement against environmental crimes can be said to be similar to law enforcement applied to ordinary crimes, which does not address environmental aspects and other aspects of victims due to environmental damage